A Study of Cylindrical Surface Grinding Under Minimum Quantity Lubrication (MQL) Conditions - Mohan kumar , R (International Journal of Psychosocial Rehabilitation, 2017)
Abrasive material removal processes is high power consuming and results in high temperatures. Effective lubrication and cooling is necessary to ensure temperature levels do not become excessive, flood lubrication is used, but this fluid delivery system increase production cost due to fluid purchase and disposal. Moreover, waste fluids have a negative environmental impact. Minimum Quantity Lubrication (MQL) method is effective lubrication method where a small amount of fluid is directed into the machining area in the form of liquid droplets with compressed air. This paper presents a comparative study of three cooling methods: conventional flood cooling, dry grinding and grinding with MQL. AISI/ SAE - 4340 steel will be ground with a general purpose alumina wheel. Results obtained demonstrate that MQL can deliver a comparable performance to flood delivery.